Determination of Repurchase Intention for Transjakarta Bus: Analysis of Service Experience, Information Quality, and Service Innovation - Aang Gunawan; Yuliantini Yuliantini; Olfebri Olfebri; Basri Fahriza (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
sssssssssssssssss